THE SELF-DIRECTED NURSE: DEVELOPING AND ASSESSING AN EDUCATIONAL BOOKLET FOR AUTONOMOUS LEARNING IN NURSING EDUCATION - Fatima , Ahmed Hassan; Aisha , Ibrahim Abdel-Hamid (Research Journal of Health, Medicine and Nursing, 2024)
Contemporary educational trends emphasize a shift from artificial to deep learning, from passive to active learning, and from teacher-dependent instruction to self-directed learning (SDL). In the context of nursing education, this transformation is paramount for preparing students to deliver comprehensive care to diverse patient populations. SDL equips students with the individual capabilities to plan their learning, identify suitable approaches, and discern the necessary resources and tools. SDL is underpinned by intrinsic motivation, veracity, conscientiousness, persistence, and diligence, all of which foster the development of nursing professionals. This article delves into the critical role of SDL in nursing education, shedding light on its capacity to enhance students' knowledge, skills, and professional values, ultimately enabling them to provide holistic patient care.